Examining intentions to engage in sun protective behaviors among Latino day laborers: An application of the theory of planned behavior - Javier Francisco Boyas; Jana L. Woodiwiss; Vinayak K. Nahar (Tabriz University of Medical Sciences, 2021)
Background: The past two decades has revealed an unprecedented increasing incidence of skin cancer within the Latinx population. Although Latino day laborers (LDLs) are at heightened risk for developing skin cancer because of the outdoor work in which they engage, there is limited research examining their intentions to engage in sun protective behaviors (SPBs). Therefore, this study sought to assess the explanatory power of the theory of planned behavior (TPB) to identify attitudinal, subjective norms, and perceived behavioral control factors associated with intentions to engage in SPB among LDLs. Methods: This cross-sectional retrospective study consists of a non-random convenience,community-based, sample of 137 LDLs residing in Mississippi and Illinois. Data were collected using a self-report survey centered on health practices and sun-protective behaviors. Results: Findings revealed that five significant factors shaped intentions to engage in SPBs, including barriers to engaging in SPBs (β =.30, P<0.001), benefits of engaging in SPBs (β =.27,P<0.001), education (β=0.20, P<0.01), and acculturation (β=0.18, P≤0.05). The independent variables tested in the model accounted for 42% of the change in intentions to engage in SPBs. Conclusion: This study demonstrates TPB's usefulness for predicting future intentions to engage in SPBs among LDLs. Moreover, the strongest factor associated with predicting intentions to engage in SPBs among LDLs was perceived behavioral control. Thus, since SPBs are malleable, emphasis is placed on implementing interventions for this population that promote intentions and address perceived behavioral control.